Peran Teknologi dalam Preservasi Arsip Vital: Tinjauan Literatur Sistematis - Widiyanti, Wiwid; Safii, Moh. (Literatify : Trends in Library Developments, 2025)
This study is a systematic literature review aimed at exploring the role of technology in protecting vital records. Vital records are documents whose existence is a fundamental prerequisite for the continuity of the records creator’s operations. They are irreplaceable and cannot be restored once damaged. Using a systematic literature review method, the researcher examined various articles relevant to the research topic. The findings show that digitization, as a form of technological application, can enhance accessibility, protect records from loss and damage, and serve as a means of disaster mitigation. Unfortunately, several challenges remain, including the lack of skilled human resources, inadequate equipment, and low public awareness regarding the importance of preserving vital records.